Analysis of Human Resources Competencies in Improving Employee Performance at Woori Saudara Bank KCP Sumedang - Umay Suniar (Journal of Bussines Management Basic, 2023)
Human resource management is defined as the science and art of managing the relationship and role of labor to be ef ective and ef icien by using human abilities in order to achieve goals. This research was conducted with the aim of knowing the competence of human resources in improving employee performance. The method used in this research is a qualitative methode using data collection techniques through observation, interviews, and documentation. Data obtained directly from employees of Woori Saudara Bank KCP Sumedang. The sampling technique used is purposive sampling which is analyzed through dimensions and indicators. The results of this study are human resource competencies in improving enployee performance carried out by Bank Woori Saudara KCP Sumedang is good but still not optimal. This is because employees are too focused on the assigned task targets, without balancing them by developing their potenci